Crossing borders of motivation: Exploring Chinese students’ intrinsic and extrinsic drivers for UK master’s degrees - Ma, Ying; Han, Feifei; Guo, Jiesi (Journal of International Students, 2026)
Globalization has increased the popularity of international master’s degrees, especially among Chinese students in the UK, driven by both intrinsic and extrinsic motivations. However, existing studies often overlook these motivations from a psychological needs perspective. This study addresses this gap using self-determination theory (SDT) to explore the motivations of six Chinese master’s students in education in the UK through semi-structured interviews and NVivo 14 analysis. The results show that intrinsic motivations include personal interests and cultural experiences, whereas extrinsic motivations involve career prospects, educational advantages, and influences from peers, family, teachers, and agencies. SDT’s psychological needs—autonomy, competence, and relatedness—are crucial in shaping intrinsic motivation and the internalization of extrinsic motivation. The findings emphasize the need for educational institutions to create supportive environments that fulfill these psychological needs, thereby enhancing students’ motivations and success in international education. Future research should explore different disciplines, master’s programs, and changes in motivations over time.